Early-Life Environment Influence on Late-Onset Alzheimer’s Disease - Gauvrit, Thibaut; Benderradji, Hamza; Buée, Luc; Blum, David; Vieau, Didier (Frontiers in Cell and Developmental Biology, 2022)
With the expand of the population’s average age, the incidence of neurodegenerative disorders has dramatically increased over the last decades. Alzheimer disease (AD) which is the most prevalent neurodegenerative disease is mostly sporadic and primarily characterized by cognitive deficits and neuropathological lesions such as amyloid-beta (A-β) plaques and neurofibrillary tangles composed of hyper- and/or abnormally phosphorylated Tau protein. AD is considered a complex disease that arises from the interaction between environmental and genetic factors, modulated by epigenetic mechanisms. Besides the well-described cognitive decline, AD patients also exhibit metabolic impairments. Metabolic and cognitive perturbations are indeed frequently observed in the Developmental Origin of Health and Diseases (DOHaD) field of research which proposes that environmental perturbations during the perinatal period determine the susceptibility to pathological conditions later in life. In this review, we explored the potential influence of early environmental exposure to risk factors (maternal stress, malnutrition, xenobiotics, chemical factors…) and the involvement of epigenetic mechanisms on the programming of late-onset AD. Animal models indicate that offspring exposed to early-life stress during gestation and/or lactation increase both AD lesions, lead to defects in synaptic plasticity and finally to cognitive impairments. This long-lasting epigenetic programming could be modulated by factors such as nutriceuticals, epigenetic modifiers or psychosocial behaviour, offering thus future therapeutic opportunity to protect from AD development.